ANALISA KEKUATAN TARIK PADA HASIL PROSES PENGECORAN NOZZLE UNTUK BRAKE COUPLING MENGGUNAKAN METODE CETAKAN PASIR JOLT SQUEEZE - Aji Abdillah Kharisma; Abdul Rahman Agung Ramadhan (Asosiasi Dosen Muda Indonesia, 2024)
Sand casting is one of the metal casting methods that has been developed and is still being improved. Sand casting is a type of metal casting that use sand molds. There are several ways to make sand casting, However, this study use the jolt squeeze technique to create complex product forms such as the nozzle component of the air brake coupling. FCD 500 nodular cast iron alloy castings are used in the production of brake coupling nozzles. The goal of this research focuses on the metal casting technique for nozzle products for brake coupling, and then continue with the tensile testing procedure. Tensile testing utilizing JIS Z 2201 standards with two sampels with different diameters, specifically 12,46 mm and 12,79 mm, and material types FCD 500-1 and FCD 500-2. The research results show the sequence of the nozzle metal casting process for brake couplings, through the stages of designing, constructing models and cores, making molds, melting, pouring, fettling and finishing, and quality control. Tensile stress values of 525 N/mm2 and 546,189 N/mm2 were obtained for each FCD 500-1 and FCD 500-2 sampels, with force loads of 64000 N and 70130,66 N, respectively.